2008
DOI: 10.1111/j.1365-2125.2007.03078.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the increase in 4β‐hydroxycholesterol concentration during carbamazepine treatment of paediatric patients with epilepsy

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• CYP3A4 converts cholesterol into 4b-hydroxycholesterol.• We have suggested that 4b-hydroxycholesterol could be used as a clinical marker for CYP3A4 activity aiding in dose adjustments.• The kinetics of 4b-hydroxycholesterol formation is not known, however, and must be determined in order to establish under what conditions 4b-hydroxycholesterol can be used as a CYP3A marker. WHAT THIS STUDY ADDS• The concentration of 4b-hydroxycholesterol increases very slowly during CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 24 publications
5
50
0
Order By: Relevance
“…There were significantly lower 4b-hydroxycholesterol levels in men than in women (P , 0.05). dmd.aspetjournals.org in studies on CYP3A induction (Kanebratt et al, 2008;Wide et al, 2008;Habtewold et al, 2012), showing good concordance with the response in other markers of CYP3A activity such as quinine metabolic ratio (Kanebratt et al, 2008) or the 6b-hydroxycortisol-to-cortisol ratio in urine (Mårde Arrhen et al, 2012). CYP3A4 expression is regulated by a complex network of transcription factors, e.g., the (VDR), pregnane X receptor, and constitutive androstane receptor (Drocourt et al, 2002).…”
Section: Downloaded Frommentioning
confidence: 71%
“…There were significantly lower 4b-hydroxycholesterol levels in men than in women (P , 0.05). dmd.aspetjournals.org in studies on CYP3A induction (Kanebratt et al, 2008;Wide et al, 2008;Habtewold et al, 2012), showing good concordance with the response in other markers of CYP3A activity such as quinine metabolic ratio (Kanebratt et al, 2008) or the 6b-hydroxycortisol-to-cortisol ratio in urine (Mårde Arrhen et al, 2012). CYP3A4 expression is regulated by a complex network of transcription factors, e.g., the (VDR), pregnane X receptor, and constitutive androstane receptor (Drocourt et al, 2002).…”
Section: Downloaded Frommentioning
confidence: 71%
“…Among them, 4b-hydroxycholesterol was first reported to be formed solely by CYP3A4 (Bodin et al, 2001). Markedly elevated concentrations of 4b-hydroxycholesterol were found in patients treated with CYP3A4 inducers (Niemi et al, 2006;Josephson et al, 2008;Wide et al, 2008;Diczfalusy et al, 2009;Goodenough et al, 2011), and decreased concentrations have been detected in patients treated with CYP3A4 inhibitors (Josephson et al, 2008;Lütjohann et al, 2009;Goodenough et al, 2011). Furthermore, a relationship between blood 4b-hydroxycholesterol concentration and the number of active CYP3A5*1 alleles has been demonstrated, suggesting that 4b-hydroxycholesterol is not only formed by CYP3A4, but also by CYP3A5 .…”
Section: Introductionmentioning
confidence: 93%
“…8 Its plasma concentration increases in subjects treated with known CYP3A4 inducers such as carbamazepine, phenytoin, phenobarbital, rifampicin, ursodeoxycholic acid and efavirenz. 8,[30][31][32][33][34][35] It was also shown that inhibitors of CYP3A4, ritonavir and itraconazol, reduce the plasma level of 4b-hydroxycholesterol. 35,36 However, recently, TomalikScharte et al 37 reported a weak correlation between cholesterol-and midazolam-based CYP3A metrics and hence questioned the validity of 4b-hydroxycholesterol as a CYP3A biomarker.…”
Section: Cyp3a Markermentioning
confidence: 99%